PRO INDIGENOUS COMMUNITY FORESTRY POLICY: A SOLUTION - Antoh, Alfred (Advances in Social Sciences Research Journal, 2021)
The Papuan people have always lived and interacted with the forest. The forest is a place to live where almost all of their needs are taken from the forest. Today's forest management has far-reaching impacts on increasingly marginalized communities. The purpose of this paper is to present thoughts on a community-friendly forest management model by taking into account the advantages and disadvantages when forests are managed by communities to improve their welfare. This paper generates an idea about the importance of collaborative management to increase the role of the community as a solution. Taking into account the communal nature of the forest tenure system in Papua, it is necessary to take strategic steps to protect forest resources in a targeted manner.